Dampak Psikologis Janda Perkawinan Model Komunitas Samin Studi Kasus di Kudus Jawa Tengah - Moh Rosyid; Lina Kushidayati (Jurnal Pemikiran Sosiologi, 2021)
The purpose of this article is portraying psychological impact of divorce for Samin people whose marriage is unregistered. Data are gathered through observation and interview among the leader and Samin people. Samin people do not register their marriage and thus, they do not undertake the regulation on the minimum age for marriage. Once divorce occurs, the wife receives psychological impacts: rumors of cohabitation (kumpul kebo), does not receive inheritance, rumors of illegal marriage. Some of Samin people try to find the way to have marriage certificate, thus register their community as a local religion. On April 25th, 2019, for the first time, the Office for Civil Affairs of Kudus issued marriage certificate for Samin people. Kudus government should pay attention to the minority rights.